Mierzenie i ocena wyników działalności jednostek samorządu terytorialnego - koncepcja i metodologia - Kozuń-Cieślak, Grażyna (Measurement and Evaluation of the Local Government Performance - Concept and Methodology, 2009)
Rationality of public money spending is a necessary condition of the government efficient functioning as well as it builds bases of public trust. Examining the efficiency of public sector requires to determine methods of measuring public entities performance, what is particularly difficult because of the specific nature of their activities. This study aims to provide the concept of how to measure the efficiency of the local government performance
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 119-126